ОРТА ӘСИРЛЕРДЕГИ ҚАРАҚАЛПАҚ МӘМЛЕКЕТЛИГИН ҚӘЛИПЛЕСТИРИЎДЕ УЛЛЫ БИЙ, УЛЛЫ ӘМИР ЕДИГЕ БАТЫРДЫҢ ТУТҚАН ОРНЫ (Тарийхый-фольклорлық әдебиятлар тийкарында) - Алламбергенов, К. (SCIENCE and SOCIETY, 2020)
In the article, on the basis of authentic facts, it is described the ethno-genetical origin of the Karakalpak batir, a vicar, leading a large family of clans – Edige, and it is also proved that he comes from a part of clan Akmangit of the Karakalpak clan Mangits, the place of his birth and life, his homeland is the territory of modern Karakalpakstan. The author of the article shows a great role of Edige in the history of struggle of the Turkic peoples for the national statehood and independence, and he comes to the conclusion that Edige is the founder of Karakalpak statehood in the middle ages.
Keywords: the 40-th of the XIV-th century; the South Aral seaside; waterlessness; Kerder; White Horde; Edil-Jayik; hero Edige